ХАРАКТЕРИСТИКИ КОРПУСНОЙ ЭЛЕКТРОИЗОЛЯЦИОННОЙ СИСТЕМЫ АСИНХРОННЫХ ЭЛЕКТРИЧЕСКИХ МАШИН НА РЕЗОНАНСНОЙ ЧАСТОТЕ - Беспрозванных, А.В.; Костюков, И.А.; Рогинский, А.В. (Інститут електродинаміки НАН України, Київ, 2019)
A T-shaped equivalent circuit of an asynchronous phase motor with a deaf connection into the “star” of the stator winding phases is presented. The calculated and experimental frequency dependences of the quality factor of the “phase-phase” circuit as a function of the dielectric loss tangent of the cabinet insulation are given. It was found that at the resonant frequency in the inductance measurement mode, the characteristics of the electrically insulating system are significantly different in comparison with the measurement mode of the capacitance of the housing system of the electric machine. References 22, table 1, figures 5.